ANALISIS PEMIKIRAN HENRI LEVEBVRE TENTANG RUANG DALAM ARSITEKTUR MODERN: SUATU PERSPEKTIF SOSIOLOGIS - Djaja Hendra (Jurnal Ilmiah Mimbar Demokrasi, 2018)
This article was trying to understand Henri Lefebvre’s thinking about space. Space means not what scientists think. Is space the same as everyday life, or is it different. Then, space means what and where Lefebvre pours space in his thoughts. What does Lefebvre mean about modern architecture and what is the diffence with traditional architecture and what kind of space to place in both types of architecture. Who are the characters close to Lefebvre and who are the figures he influences. Concerned, the figures who are also the thinkers, Lefebvre inti the camp of where and who most preferred his thoughts ranging from classical sociologist and modern sociology and the reasons he put forward.